Bond market modelling using a trinomial tree - Artamonova, Jelena; Leipus, Remigijus (Lietuvos matematikos rinkinys, 2004)
In this paper a generalization of the discrete-time Ho–Lee model to the trinomial case is considered. The necessary and sufficient conditions for such a bond model to be arbitrage-free and path independent are established.